(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The impact of social media marketing on internet merchants is examined in this article. Onlinemerchants have realized the possibility of using social media as an effective marketing tool as a result ofthe social media platforms’ exponential expansion and the rise in user engagement. This investigationlooks at the many effects social media marketing has on online retailers, such as improved brandrecognition, customer engagement, greater sales, and customer retention. The essay also discussespossible obstacles and offers doable advice for online merchants that want to utilize the advantages ofsocial media marketing in their entire marketing plan. The sample comprises of 150 online businessowners who reported their successes or failures with social media marketing for their Indian-basedcompanies. Pilot tests, reliability analyses, validity analyses, descriptive statistical analyses, Pearson’scorrelation analyses, and multiple regression analyses are the requirement analysis tests that areemployed. Software called Statistical Package for Social Sciences (SPSS) Version 25.0 is utilized for thedata analysis approach. Four independent factors, including customer feedback, communication,content sharing, and customer connections, will be assessed to see how they affect online firms’ salessuccess. The study’s findings indicate that customer feedback has no direct impact on salesperformance, while communication and content sharing have an indirect impact. However, customerrelationships have a direct impact on sales performance of online businesses in India.